Determinant of Mahathir's Foreign Policy Towards Palestine Conflict - Abdul Majid Hafiz, Mohamed; Ahmad Shariff, Haron; Mohd Afandi, Salleh; Abdullahi Ayoade, Ahmed (2016)
Malaysia during the tenure of Tun Mahathir Mohammed as the premier always has put Palestine in the special place. It was during Mahathir’s era that sees the high commitment of the government towards the Palestine – Israel crisis. This paper will attempt to analyze the reasons that influence Mahathir decisions or also known as determinants of Mahathir’s foreign policy towards the Palestine conflict.